Characterization of Alternaria alternata, a carbendazim degrading strain - Maganhotto de Souza Silva, Célia Maria; Soares de Melo, Itamar (Pesquisa Agropecuaria Brasileira, 1997)
One Alternaria alternata strain, isolated from benomyl treated soil was found to degrade the fungicide carbendazim which is a product of benomyl hydrolysis. This strain was characteriezed in the following aspects: mycelial growth and sporulation, cytological aspects and electrophoresis of total proteins and esterase. It was observed that the strain had significative mycelial growth in the V-8 juice, malt-agar, Sabouraud, oat-agar and MC de Pontecorvo media and that sporulation in different photoperiods was variable, but it was satisfactory in the absence of light. This strain, called Alt A, presents ovoid spores with length varying from 15.4 to 38.4 mm and diameter from 5.8 to 9.6 mm with one to five transversal septa. When electrophored by total proteins and esterase in polyacrilamide gels, and compared with other two phytopathogenic Alternaria alternata strains (CCT 1250 and CCT 3823), the strain Alt A presented typical band patterns, which differed from those of the other two strains. This could be an indication of genetic variation among the strains.